Roles and Challenges of Women in Tourism Sector of Western Nepal: A Micro- Ethnographic Study - KC, Sony (Nepal Tourism and Development Review, 2013)
This paper examines the association of women and men in tourism, with particular focus on women’s choices in picking roles, and challenges they encounter based on the roles they perform. This is a qualitative research paper based on the perceptions and expectations of women. It utilizes a month’s field data from a few villages of Western Nepal. The information is extracted from key informant interviews, participant observations, focus group discussions along with existing literatures and policy document reviews. Findings reveal that roles are determined by factors such as education, family background, physical condition, language, and the ability to set one’s own criteria. The gender-based roles are determined by demands of tourists and the demand for the nature of work. Unbearable workloads as referred to were undone dishes, laundry, children’s demand and pressure from in-laws. Challenges such as lack of secure job, bullying by close relatives and the ultimate failure in balancing family and work were mentioned. Families were determined as the crucial role players in shaping the lives of these women who perceived that a little support from family members made their roles easier. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7379 Nepal Tourism and Development Review Vol.2(1) 2012 32-59